Pengaruh Brand Liking dan Brand Competence Terhadap Brand Loyalty Pada Skincare Somethinc di Beautebox Tasikmalaya - Yasinta Sabilla; Depy Muhamad Pauzy; Suci Putri Lestari (CV. ULIL ALBAB CORP, 2023)
This study aims to determine and analyze the effect of brand liking and brand competence both simultaneously and partially on Brand Loyalty in Skincare Somethinc Beautebox Tasikmalaya products. The method used in this research is quantitative with a descriptive approach. With a research sample of 100 consumers as respondents. The data used is using primary data. The analytical tool used in this study is multiple linear regression using the SPSS version 25 support application. The test results show that partially the variables used in the study, namely brand liking and brand competence, have a significant effect on Brand Loyalty for Skincare Somethink Beautebox Tasikmalaya products. Simultaneously there is a positive and significant influence of brand liking and brand competence together on Brand Loyalty.